RANCANG BANGUN ALAT IDENTIFIKASI NOMINAL UANG KERTAS UNTUK TUNANETRA BERBASIS ARDUINO MEGA 2560 DENGAN OUPUT SUARA - ., Rudi Arpianto (Faculty of Engineering, Universitas Tanjungpura, 2018)
For people with visual impairment, the only way identify banknotes of Indonesia is to rub it by the hands first. Nevertheless, in the some cases like rumpled banknotes and the newest emission of banknotes, the of identification became even harder. From the problem stated, the writer intended to help people with visual impairment to make an easier way for them in identifying banknotes by creating a device that could identify the nominal of any Rupiah’s bill. The device used TCS3200 color sensor as the input, and Arduino Mega 2560 for data processing. For the output, the IC TBA820M sound module was used. The color sensor read the base color of red, green and blue on the surface of the bottom left corner of rupiah’s bill. The base color of the bill was saved in the program and be used as a parameter to determine the nominal of the bill. Each parameter was equipped with sound program through the processing stage Arduino Mega 2560 and IC TBA820M sound module. The bills identified were those issued in2009 regardless of their condition, and new 2016 emission’s bills. The nominal identified the range of IDR 1,000 to IDR 100,000. The bills that had become the parameter was identified by the color sensor which then activated the sound module hear. The banknotes identification device that writer made were portable (can be brought in a bag) with only 5-volt DC of power.Keywords : TCS3200 Color Sensor, IC TBA820Msound module, Arduino Mega 2560